Acceptance Factors of Pneumococcal Vaccination among Adult Population: A Systematic Review - Siti Nor Mat; Norzaher Ismail; Syafiq Taib; Hasanain Faisal Ghazi; Zahir Izuan Azhar; Mohammad Saffree Jeffree; Azmawati Mohammed Nawi; Mohd Rohaizat Hassan (2018)
Received 20 July 2018 Accepted 24 August 2018 Introduction Pneumococcal disease causes considerable morbidity and mortality, including among adults. Adult pneumococcal vaccines help to prevent these burdens, yet, they are underutilized. Our objective is to systematically collect and summarize the available evidence on the potential factors that lead to pneumococcal vaccination acceptance among of adult community. Methods A systematic literature search was conducted involving studies published from January 1999 to December 2015. The studies were identified by searching electronic resources (PubMed/MEDLINE and Pro Quest database) and manual searches of references. The keywords “vaccine/ immunization”, “uptake/ coverage”, “determinant/ factor”, and “Streptococcus pneumoniae/ pneumococcus/ pneumococcal” were used. Final studies result and data were reviewed by two independent authors. Disagreement was resolved through discussion and consensus. Results A total of 171 studies were identified, only 17 studies were included in final discussion with 10 domains identified in the paper. 7 studies (41%) had reported that the provider domain, patients’ perception and socio-demographic factor have had the most effect on the pneumococcal vaccination acceptance rate. In addition, only 18% (3) of reviewed papers had highlighted that socio-economic was a factor influenced the pneumococcal vaccination acceptance while 24% (4 studies) were attributed to the comorbid domains. Conclusions Healthcare provider and patients’ perception about pneumococcal vaccination for adult population are significant domains which influence the acceptance towards vaccination. Strong recommendations from healthcare provider for pneumococcal vaccination would be an important step to increase vaccination acceptance among the population.